ä½¿ç”¨å¤šåª’ä½“æ•™å¦æ³•æé«˜Kemala Bhayangkariåˆä¸ä¸€å¹´çº§å¦ç”Ÿ æ±‰è¯è¯æ±‡å¦ä¹ èƒ½åŠ› - Sari, Novita; Thamrin, Lily; Khion, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Â  æ‘˜è¦ï¼šæœ¬æ–‡çš„ä¸»è¦ç›®çš„æ˜¯äº†è§£å¤šåª’ä½“æ•™å¦æ³•å¯¹å¦ç”Ÿå¦ä¹ æ±‰è¯è¯æ±‡çš„å½±å“ï¼Œäº†è§£å¦ç”Ÿå¯¹å¤šåª’ä½“æ•™å¦çš„ååº”ã€‚ç ”ç©¶å¯¹è±¡æ˜¯Kemala Bhayangkariåˆä¸ä¸€å¹´çº§å¦ä¹ Â Â Â Â  æ±‰è¯çš„ççº§ï¼Œä¸€å…±30åå¦ç”Ÿï¼ˆç”·ç”Ÿ12åï¼›å¥³ç”Ÿ18åï¼‰ã€‚ç ”ç©¶æ–¹æ³•æ˜¯æµ‹è¯•æ³•ã€å®žéªŒæ³•ï¼ˆä½¿ç”¨å¤šåª’ä½“æ•™å¦æ³•ï¼Œå¦‚ï¼šç”µè„‘ï¼ŒæŠ•å½±æœºå’ŒéŸ³ç®±ï¼‰å’Œè°ƒæŸ¥é—®å·ã€‚æ ¹æ®Â Â  æœ¬æ–‡ç ”ç©¶çš„ç»“æžœï¼Œå¦ç”Ÿå¯¹å—åˆ°å¤šåª’ä½“æ•™å¦æ³•å‰åŽçš„æ±‰è¯è¯æ±‡å¦ä¹ èƒ½åŠ›ï¼Œä½¿ç”¨Â Â  å¤šåª’ä½“æ•™å¦æ³•æé«˜äº†å¦ç”Ÿå¦ä¹ è¯æ±‡çš„èƒ½åŠ›ï¼Œå—åˆ°å¤šåª’ä½“æ•™å¦æ³•ä¹‹åŽï¼Œå¦ç”Ÿçš„Â Â  æµ‹è¯•æˆç»©ä¹Ÿéšä¹‹å¢žé•¿ï¼Œæ•ˆæžœæ˜¾è‘—æ›´å¥½ã€‚æ¤å¤–ï¼Œåœ¨æ•™å¦è¿‡ç¨‹ä¸ä½¿ç”¨å¤šåª’ä½“æ•™å¦æ³•æœ‰åŠ©äºŽå¢žå¼ºå¦ç”Ÿå¦ä¹ æ±‰è¯è¯æ±‡çš„èƒ½åŠ›ï¼Œæ¿€å‘å¦ä¹ å…´è¶£ï¼Œæé«˜å¦ä¹ æˆç»©ï¼Œå¢žå¼ºÂ Â  è‡ªä¿¡å¿ƒï¼Œå¹¶ä¸”å¦ç”Ÿæ˜“äºŽæŽ¥å—å¤šåª’ä½“æ•™å¦æ³•ã€‚ Â  å…³é”®è¯ï¼šå¤šåª’ä½“ï¼Œè¯æ±‡ï¼Œæ•™å¦æ³• Â  Abstrak : The purpose of this research is to know the effect of multimedia methods to learn Chinese vocabulary of students, to know the students' response to the application of multimedia methods. The object of this research is SMP Kemala Bhayangkari, with total students were 30 students (12 male; 18 female). The research method is a method of test, practice (the use of multimedia teaching methods, such as: computer, projector and speaker) and a questionnaire. According to the results of this research, the ability of students to learn Chinese vocabulary to use before and after the application of multimedia teaching methods, the use of multimedia methods improve students' Chinese vocabulary, after the application of multimedia methods, student test scores also increased, the effect is significantly better. Moreover, in the process of teaching the use of multimedia teaching methods will help to improve the ability of students to learn Chinese vocabulary, stimulate interest in learning, improve academic achievement, improve self-confidence, and the use of multimedia easily accepted by students. Â  Key words: multimedia, vocabulary, teaching Â